The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21472/bjbs.040702
|View full text |Cite
|
Sign up to set email alerts
|

Cell water content and lignification in maize regulated by rhizobacteria under salinity

Abstract: Abstract. Inoculation of plant growth promoting rhizobacteria (PGPR) Pseudomonas aeruginosa and Bacillus megaterium in maize plant under salinity stress was analyzed for its growth promotion efficacy and induction of physiological mechanism. In this study effect of these isolates were focused on the cellular level as with lignin deposition, cell wall lignin content and cell water status of maize under salinity. Maize plants get protected from the salinity induced injury by enhancing the plant growth, regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…These compounds were found to prevent tissues from oxidative damage and enable plants to tolerate stresses (Pazoki 2015 ; Ilangumaran and Smith 2017 ; Nawaz and Bano 2020 ). Our results agreed with those obtained by Jha ( 2017 ) who reported that phenolics and flavonoids were enhanced in PGPB-inoculated maize under normal and stress conditions. Furthermore, the total antioxidant capacity was significantly ( p ≤ 0.05) increased in inoculated plants compared with the non-inoculated plants under drought stress (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These compounds were found to prevent tissues from oxidative damage and enable plants to tolerate stresses (Pazoki 2015 ; Ilangumaran and Smith 2017 ; Nawaz and Bano 2020 ). Our results agreed with those obtained by Jha ( 2017 ) who reported that phenolics and flavonoids were enhanced in PGPB-inoculated maize under normal and stress conditions. Furthermore, the total antioxidant capacity was significantly ( p ≤ 0.05) increased in inoculated plants compared with the non-inoculated plants under drought stress (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…There are few data on the effect of PGPM on the lignification of plant cells. For example, the rhizobacteria Pseudomonas aeruginosa and B. megaterium protected maize plants from salt stress-caused damages along with regulating cell water content, phenols, flavonoids, and antioxidant enzymes, also through lignification [ 70 ]. Inoculation with the plant growth-promoting rhizobacteria cytokinin-producing B. subtilis and auxin-producing P. mandelii strains resulted in a faster appearance of Casparian bands in the root endodermis and an increased growth of the salt-stressed plants [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial proliferation was assessed by measuring the optical density (OD) of the cultures at a wavelength of 600 nm. Additionally, the biotransformation potential of S. arlettae was evaluated by quantifying the presence of As +5 and As +3 in the bacterial strain's culture supernatant exhausting the Community Bureau of Reference (BCR) technique (Kazi et al, 2005).…”
Section: Screening the Rhizobacterium For As Tolerance And Biotransfo...mentioning
confidence: 99%